The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/gch2.202000010
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cell Based on Hybrid Structural SiNW/Poly(3,4 ethylenedioxythiophene): Poly(styrenesulfonate)/Graphene

Abstract: Solar energy is considered as a potential alternative energy source. The solar cell is classified into three main types: i) solar cells based on bulk silicon materials (monocrystalline, polycrystalline), ii) thin‐film solar cells (CIGS, CdTe, DSSC, etc.), and iii) solar cells based on nanostructures and nanomaterials. Nowadays, commercial solar cells are usually made by bulk silicon material, which requires not only high fabrication costs but also limited performance. In this study, the fabrication of high‐per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…As mentioned earlier, the p-type doping increases the work function of graphene and intensifies the built-in potential which results in higher PCE. [113][114][115][116][117][118][119] Since PEDOT: PSS and HNO 3 are p-type dopants for graphene, therefore in this study, the directly grown VGNH were co-doped with PEDOT: PSS and HNO 3 . Hence, the directly grown VGNH on textured-Si exhibited a higher work function of ≈4.7 eV, and consequently a higher PCE, that is, 10.97% was achieved with an active area of 0.9 cm 2 after codoping.…”
Section: Solar Cellsmentioning
confidence: 99%
“…As mentioned earlier, the p-type doping increases the work function of graphene and intensifies the built-in potential which results in higher PCE. [113][114][115][116][117][118][119] Since PEDOT: PSS and HNO 3 are p-type dopants for graphene, therefore in this study, the directly grown VGNH were co-doped with PEDOT: PSS and HNO 3 . Hence, the directly grown VGNH on textured-Si exhibited a higher work function of ≈4.7 eV, and consequently a higher PCE, that is, 10.97% was achieved with an active area of 0.9 cm 2 after codoping.…”
Section: Solar Cellsmentioning
confidence: 99%
“…The enhancement could result from the low reflectance of SiNW structures for enhancing the light absorption and to large p/n junction areas for enhancing the carrier collection efficiency. 39–44 Moreover, the increase in the surface roughness of the devices using SiNWs is shown in Fig. 3c.…”
Section: Resultsmentioning
confidence: 89%
“…The enhancement could result from the low reectance of SiNW structures for enhancing the light absorption and to large p/n junction areas for enhancing the carrier collection efficiency. [39][40][41][42][43][44] Moreover, the increase in the surface roughness of the devices using Table 1 Structure and photovoltaic properties of the hybrid solar cells: short circuit current density (J sc ), open circuit voltage (V oc ), series resistance (R s ), fill factor (FF), and efficiency (PCE)…”
Section: Morphology Of Silicon Nanostructuresmentioning
confidence: 99%
“…From Table 1, where the highest performing polymer-SiNW hybrid solar cells are tabulated, it is observed that all these solar cells have PEDOT:PSS as a common polymer for SiNW array. Similarly, for each hybrid solar cell the PEDOT:PSS makes radial p-n junction with SiNW array because such radial p-n junction structure efficiently supports both the light absorption and carrier collection perpendicular to each other [41][42][43][44][45][46][47][48].…”
Section: P-n Junction Designmentioning
confidence: 99%
“…Shows the SEM images of side-view and top-view (inset) of SiNW fabricated by chemical etching method. When etching-time is doubled (30 min to 60 min) then the length of SiNW is also double (from 4 µm to 8 µm) but the SiNWs of higher length are agglomerated[48].…”
mentioning
confidence: 99%